2017
DOI: 10.3758/s13421-017-0722-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-prioritization and perceptual matching: The effects of temporal construal

Abstract: Recent research has revealed that self-referential processing enhances perceptual judgments — the so-called self-prioritization effect. The extent and origin of this effect remains unknown, however. Noting the multifaceted nature of the self, here we hypothesized that temporal influences on self-construal (i.e., past/future-self continuity) may serve as an important determinant of stimulus prioritization. Specifically, as representations of the self increase in abstraction as a function of temporal distance (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
4
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 123 publications
(243 reference statements)
7
78
4
7
Order By: Relevance
“…Model comparisons showed that the best fitting model required the three-parameter model (see Supplementary Materials), consistent with the findings in prior research (Golubickis, Falben, Cunningham, & Macrae, 2018;Golubickis et al, 2017). We then extracted the parameters for each condition and tested the hypothesis by analyzing the posterior probability density of the parameters across the conditions.…”
Section: Diffusion Modellingsupporting
confidence: 77%
See 2 more Smart Citations
“…Model comparisons showed that the best fitting model required the three-parameter model (see Supplementary Materials), consistent with the findings in prior research (Golubickis, Falben, Cunningham, & Macrae, 2018;Golubickis et al, 2017). We then extracted the parameters for each condition and tested the hypothesis by analyzing the posterior probability density of the parameters across the conditions.…”
Section: Diffusion Modellingsupporting
confidence: 77%
“…edu/hddm_docs; Wiecki et al, 2013), with a default group prior roughly matching the parameter values reported by Matzke and Wagenmakers (2009). Based on previous research (e.g., Golubickis et al, 2017), we fixed the threshold a because it has been suggested that threshold should remain constant throughout a task when the luminance of the stimuli is constant across the trials. Note that we used the response coded approach (see the Deviations from Registration in the Supplementary Materials).…”
Section: Diffusion Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a perceptual-matching task, researchers have shown that participants make faster and less errant responses to stimuli related to the self than other persons. Critically, this effect has been replicated on numerous occasions, with self-prioritization extending to a wide range of stimuli, including: geometric shapes (Desebrock, Sui, & Spence, 2018;Enock, Sui, Hewstone, & Humphreys, 2018;Golubickis et al, 2017;Schäfer, Frings, & Wentura, 2016;Schäfer, Wentura, & Frings, 2017;Schäfer, Wesslein, Spence, Wenura, & Frings, 2016;Sui et al, 2012Sui et al, , 2013Sui et al, , 2014, badges of sports teams (Moradi, Sui, Hewstone, & Humphreys, 2015), objects (Schäfer, Wentura, & Frings, 2015), computer-generated avatars (Mattan, Quinn, Apperly, Sui, & Rothshtein, 2015), Gabor patches (Macrae, Visokomogilski, Golubickis, & Sahraie, 2018;Stein et al, 2016), lines (Siebold et al, 2015), and faces (Payne, Tsakiris, & Maister, 2017). In addition, self-prioritization has been reported across various sensory modalities (Frings & Wentura, 2014;Schäfer et al, 2015Schäfer et al, , 2016b.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, using breaking continuous flash suppression (b-CFS) to examine the ease with which items (i.e., Gabors) access consciousness during a stimulus-localization task, Stein et al (2016) observed no effect of self-relevance on the time taken for Gabors to overcome interocular suppression. Interestingly, however, contrasting Stein et al (2016), Macrae, Visokomogilski, Golubickis, Cunningham, and Sahraie (2017) demonstrated enhanced access to visual awareness for self-relevant (vs. other-relevant) shapes when participants performed a stimulus-identification task. What this latter finding suggests is that self-prioritization is contingent upon task instructions (e.g., stimulus localization vs. stimulus identification) that draw attention to the self-relevance of target-object associations in memory.…”
mentioning
confidence: 89%